Effects of Trade-Based Money Laundering on Banking Sector : https://doi.org/10.5281/zenodo.16883293 - Syeda Aqsa Jawaid; Dr. Muhammad Muzammil; Haris Hanif (`, 2025)
Trade-Based Money Laundering (TBML) is one of the most intricate and underreported forms of illicit financial activity, posing substantial risks to global banking systems. This study investigates the effect of TBML on the banking sector, focusing on how increasing occurrences influence share prices i.e. a proxy for investor confidence, and overall bank valuation. Using a quantitative design, secondary financial data from publicly listed banks were analysed, incorporating variables such as Earnings Per Share (EPS), Dividend Yield, and TBML event occurrences. Econometric techniques, including descriptive statistics, correlation, and multiple regression in EViews, were employed to assess causal relationships between financial indicators and stock performance. Findings reveal that TBML incidents have a statistically significant long-term negative impact, driven by market inefficiencies, information asymmetry, and delayed regulatory disclosures. The study addresses a critical gap in financial crime literature and calls for enhanced regulatory transparency, investor education, and robust compliance measures to mitigate systemic risks. Keywords: Trade-Based Money Laundering, Banks, Banking Sector, Stock Price, Earnings Per Share, Dividend Yield, Market Confidence, Pakistan.